Calcineurin signaling promotes takotsubo syndrome - Bruns, Bastian; Antoniou, Marilena; Baier, Irena; Joos, Maximilian; Sevinchan, Meryem; Moog, Marie-Christine; Dieterich, Christoph; Friederich, Hans-Christoph; Herzog, Wolfgang; Frey, Norbert; Schultz, Jobst-Hendrik; Backs, Johannes (Nature cardiovascular research, 2023)
Takotsubo syndrome (TTS) is an acute heart failure syndrome that mimics the symptoms of acute myocardial infarction and is often preceded by emotional and/or physical stress. There is currently no treatment for TTS. Here we show that injection of 2.5 mg kg−1 of epinephrine (EPI) into mice recapitulates numerous features of human TTS, including increased myocardial damage and mortality in males. Gene set enrichment analysis of myocardial RNA sequencing after EPI injection revealed significant enrichment of calcineurin-dependent pro-inflammatory gene networks, which was more pronounced in male than in female mice, in agreement with observed sex discrepancies in the mouse phenotype. An increase in calcineurin activity was detected in the circulating cells of patients with TTS, suggesting a systemic nature of the syndrome. Preventive and therapeutic treatment of mice injected with EPI using calcineurin inhibitors cyclosporine and tacrolimus improved heart function and reduced myocardial injury. Our findings suggest that calcineurin inhibition could be a potential therapy for TTS.